2021
DOI: 10.1016/j.ypmed.2021.106596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on cervical cancer screening: Challenges and opportunities to improving resilience and reduce disparities

Abstract: The COVID-19 pandemic has a major impact on a wide range of health outcomes. Disruptions of elective health services related to cervical screening, management of abnormal screening test results, and treatment of precancers, may lead to increases in cervical cancer incidence and exacerbate existing health disparities. Modeling studies suggest that a short delay of cervical screening in subjects with previously negative HPV results has minor effects on cancer outcomes, while delay of management and treatment can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 86 publications
(95 reference statements)
3
81
0
2
Order By: Relevance
“…This finding was consistent with that of a study in a safety net hospital in San Francisco, where there was a reduction in the cumulative number of mammograms compared with the pre-COVID-19 era [22]. Another study reported that cervical cancer screenings declined after the national emergency declaration and remained 35% below the historical average [31]. The screening participation rate for colorectal and gastric cancer decreased more in women aged 70 years and older than in men of the same age group (percentage change: -12.4% vs. -16.6% for colorectal cancer; -12.0% in men vs. -14.7% in women for gastric cancer) (Supplementary Tables 1-2).…”
Section: E P U B a H E A D O F P R I N Tsupporting
confidence: 88%
“…This finding was consistent with that of a study in a safety net hospital in San Francisco, where there was a reduction in the cumulative number of mammograms compared with the pre-COVID-19 era [22]. Another study reported that cervical cancer screenings declined after the national emergency declaration and remained 35% below the historical average [31]. The screening participation rate for colorectal and gastric cancer decreased more in women aged 70 years and older than in men of the same age group (percentage change: -12.4% vs. -16.6% for colorectal cancer; -12.0% in men vs. -14.7% in women for gastric cancer) (Supplementary Tables 1-2).…”
Section: E P U B a H E A D O F P R I N Tsupporting
confidence: 88%
“…There were few opportunities for primary and secondary prevention of cervical cancer and the availability of telehealth visits did not address the need for in-person examination during the pandemic. 2…”
Section: The Unmeasured Impact Of Medical Care Missed or Delayed By C...mentioning
confidence: 99%
“…The COVID-19 pandemic has also caused disruptions to nonemergency procedures, including cervical cancer screening. 38 Moreover, access to providers who offer HPV testing is a significant obstacle for women in low-resource settings.…”
Section: Early Detection For the Preventive Care Of Hpv-related Cancermentioning
confidence: 99%